Residential Care in Los Angeles: evaluating the spatial distribution of facilities and neighbourhood access to care among older adults. Issue 3 (4th March 2019) - Frochen, Stephen; Ailshire, Jennifer; Rodnyansky, Seva
ABSTRACT: Residential care has increased in number of facilities and has grown in density in urban areas, yet it is disproportionately dispersed in cities and only beginning to meet the current long-term care need of older adults as an alternative to institutional and in-home care. California State Department of Social Services residential care facility data were linked with Los Angeles County census tract data to examine the spatial distribution of facilities through hot spot analysis of clusters of small and large facilities and zero-inflated negative binomial regression of census tract facility counts on older age and race groups, older disabled adults, and older adults in poverty in the area. The results show clusters of large facilities west of downtown Los Angeles and clusters of small facilities in the northern suburbs of the city in the San Fernando Valley. Increases in pre- and early-retired adults and older Hispanics in census tracts are associated with the greatest decreases in facility tract capacity in the area, whereas increases in the oldest old and older disabled adults are associated with the greatest increases. Understanding spatial disparities in residential care can help local agencies and developers plan and partner in more intentional and equitable development of facilities. The greatest opportunity for such development may lie in institutional tools for eldercare facility development such as the eldercare facility ordinance of Los Angeles and development of board and care facilities in residential zones of Los Angeles and other cities.